2006
DOI: 10.1007/s10067-006-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymyositis associated with focal mesangial proliferative glomerulonephritis with depositions of immune complexes

Abstract: A 58-year-old man concurrently developed polymyositis (PM), interstitial lung disease, and nephrotic-range proteinuria. Renal biopsy revealed focal mesangial proliferative glomerulonephritis (mesPGN) with depositions of immunoglobulin and complements. A combination therapy of corticosteroid, intravenous immunoglobulin, and cyclosporine was found very effective for the patient. Glomerulonephritis associated with PM/dermatomyositis (DM) is rare. In our review of related literature, mesPGN was exclusively observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In the literature search we retrieved 15 published cases 1 , 3 , 4 , 6 , 9 , 14 , 15 , 21 , 22 , 25 29 , 31 of nephropathies documented by kidney biopsy in IM patients (Table 6 ). These cases include IgAN (n = 7), MN (n = 1), membranoproliferative glomerulonephritis (n = 1), pauci-immune crescentic glomerulonephritis (n = 2), minimal change disease (n = 2), focal segmental glomerulosclerosis lesions (n = 1), and acute tubulointerstitial nephritis (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature search we retrieved 15 published cases 1 , 3 , 4 , 6 , 9 , 14 , 15 , 21 , 22 , 25 29 , 31 of nephropathies documented by kidney biopsy in IM patients (Table 6 ). These cases include IgAN (n = 7), MN (n = 1), membranoproliferative glomerulonephritis (n = 1), pauci-immune crescentic glomerulonephritis (n = 2), minimal change disease (n = 2), focal segmental glomerulosclerosis lesions (n = 1), and acute tubulointerstitial nephritis (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cases presenting with anti-neutrophil cytoplasmic antibody-associated glomerulonephritis in the context of DM have also been reported [48][49][50]. As pointed out in previous studies [6,25], there is a tendency for mesangial proliferative glomerulonephritis to be more frequently observed in PM, while membranous nephropathy is more frequently observed in the context of DM.…”
Section: Discussionmentioning
confidence: 69%
“…As for the study by Couvrat-Desvergnes et al, they identified 14 patients who had undergone renal biopsy (6 PM, 5 DM, and 3 ASS), which revealed the presence of glomerulonephritis with various pathologic patterns including immune complex-related glomerulonephritis (n � 4), membranous nephropathy (n � 2), and IgA nephropathy (n � 2) [5]. We conducted an additional literature search and retrieved case reports describing the association of PM or DM with a variety of pathological glomerular lesions, including mesangial proliferative glomerulonephritis [21][22][23][24][25], membranous nephropathy [26][27][28][29][30][31], membranoproliferative glomerulonephritis [32], IgA nephropathy [33][34][35][36][37], diffuse proliferative glomerulonephritis [38], immune complex-type glomerulonephritis [39][40][41][42], acute interstitial nephritis [43], lipoid nephrosis and focal glomerulosclerosis [44], focal segmental glomerulosclerosis with evidence of acute tubular injury [45], sclerotic GN with fibrocellular crescent [46], and crescentic glomerulonephritis associated with malignancy [47]. Cases presenting with anti-neutrophil cytoplasmic antibody-associated glomerulonephritis in the context of DM have also been reported [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Yen et al (12) reported that 14 out of 65 patients with PM/DM had renal involvement. Takizawa et al (13) reported 21 cases of PM/DM-associated glomerulonephritis confirmed by biopsy. The diagnosis included 12 cases of glomerular proliferative glomerulonephritis, six cases of membranous glomerulonephritis, one case of minimal change g l o m e r u l o n e p h r i t i s a n d t w o c a s e s o f c r e s c e n t i c glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of PM/DM complicated with IgAN are not common. To date, 11 cases of SAMs with IgAN have been reported previously: two cases of juvenile DM (21,22), two DM (23,24), three PM (25)(26)(27), and four anti-synthetase syndrome (11,13,28). The details of the reported 11 cases are shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%